Conflict and Personality of The Main Character in Kim Yong-Hoon’s Mask Girl: A Psychological Analysis - Ginting, Sofia Ananda (Universitas Negeri Medan, 2024)
This study explores the conflict and personality of the main character, Kim Mo-mi, in the Korean drama Mask Girl directed by Kim Yong-Hoon. By employing qualitative methodology, the research investigates the internal and external conflicts faced by the main character through 30 pieces of dialogue from the script. Using theories by Kenney (1966) and McCrae & Costa (2005), the study categorizes these conflicts and analyzes Kim Mo-mi's personality traits. The findings reveal significant internal conflicts arising from her self-perception and external conflicts involving her relationships with others. The study concludes that these conflicts significantly influence Kim Mo-mi's personality, highlighting the importance of psychological analysis in literary works.